Ancient host-pathogen associations maintained by specificity of chemotaxis and antibiosis. - Nicole M Gerardo; Sarah R Jacobs; Cameron R Currie; Ulrich G Mueller (PLoS Biology)
Switching by parasites to novel hosts has profound effects on ecological and evolutionary disease dynamics. Switching requires that parasites are able to establish contact with novel hosts and to overcome host defenses. For most host-parasite associations, it is unclear as to what specific mechanisms prevent infection of novel hosts. Here, we show that parasitic fungal species in the genus Escovopsis, which attack and consume the fungi cultivated by fungus-growing ants, are attracted to their hosts via chemotaxis. This response is host-specific: Escovopsis spp. grow towards their natural host cultivars more rapidly than towards other closely related fungi. Moreover, the cultivated fungi secrete compounds that can suppress Escovopsis growth. These antibiotic defenses are likewise specific: in most interactions, cultivars can inhibit growth of Escovopsis spp. not known to infect them in nature but cannot inhibit isolates of their naturally infecting pathogens. Cases in which cultivars are susceptible to novel Escovopsis are limited to a narrow set of host-parasite strain combinations. Targeted chemotactic and antibiotic responses therefore explain why Escovopsis pathogens do not readily switch to novel hosts, consequently constraining long-term dynamics of host-parasite coevolution within this ancient association.